Equity & access : an analysis of educational leadership preparation, policy, & practice - Fowler, Denver J.; Heilig, Julian Vasquez; Jouganatos, Sarah M.; Johnson, Arvin (Leadership for school improvement, 2023)
"This book is significant in that it offers an in-depth historical analysis of educational leadership and educational policy in the United States and around the globe. The book focuses on how leadership preparation and practices as well as policy and procedures have effected and continues to effect all stakeholders including school leaders, teachers, and students. The aim of the book is to examine both the positive and negative implications (nationally and internationally) of: (1) trends in educational leadership preparation; (2) trends in educational leadership practices; (3) educational policy; and (4) the procedures and the intended/unintended consequences associated with such policies"--